Construction of Interferon-Gamma-Related Gene Signature to Characterize the Immune-Inflamed Phenotype of Glioblastoma and Predict Prognosis, Efficacy of Immunotherapy and Radiotherapy - Ji, Hang; Ba, Yixu; Ma, Shuai; Hou, Kuiyuan; Mi, Shan; Gao, Xin; Jin, Jiaqi; Gong, Qin; Liu, Ting; Wang, Fang; Liu, Zhihui; Li, Shupeng; et al. (Frontiers in Immunology, 2021)
Interferon-gamma (IFNG) has profound impacts on tumor-immune interaction and is of great clinical significance for multiple cancers. Exploring the role of IFNG in glioblastoma (GBM) may optimize the current treatment paradigm of this disease. Here, multi-dimensional data of 429 GBM samples were collected. Various bioinformatics algorithms were employed to establish a gene signature to explore immunological characteristics and genomic alterations associated with IFNG response and validate its clinical implications. In this way, a novel IFNG-related gene signature (TGFBI, IL4I1, ACP5, and LUM) that effectively characterizes the IFNG response in GBM has been constructed. The IFNG-related high-risk group was characterized by increased neutrophil infiltration and exuberant innate immune response, while the activated adaptive immune response may be frustrated by multiple mechanisms including IL4 and immune checkpoints. Notably, the IFNG pathway and its antagonistic pathways including IL4, IL10, VEGF were implicated in immune checkpoint expression. Besides, gene mutations involved in the microenvironment and stress were associated with the IFNG-related risk stratification. Moreover, the IFNG-related risk model had solid prognostic value and the potential to screen ICB and radiotherapy sensitive populations. Collectively, our study provided insights into the role of IFNG on the GBM immune microenvironment and offered feasible information for optimizing the treatment of GBM.